Pergeseran Makna Stoikisme di Kalangan Masyarakat Modern - Raihan Harahap (IKIP Budi Utomo Malang, 2023)
There has been a shift in the meaning of stoicism in modern society. Living by the principle ofstoicism has become a hot topic in recent years because it has the concept of thinking so that humans cancontrol their thoughts so that humans do not easily experience stress. Instead of teaching us to be lazy,stoicism comes as a principle that encourages us to think hard with the aim of having a better life thanbefore. The research method used in this research is literature study. Literature study aims to see the shiftingmeaning of stoicism and shed light on the true meaning of stoicism. This article is compiled based on severaljournal articles, books, and other internet sources to support the preparation with a publishing period of 10years ago. With the aim that there are no more misunderstandings or misconceptions about the meaning ofstoicism and emphasize that stoicism is not a principle that requires a person to be lazy in activities or evenin thinking. In fact, stoicism teaches us to think hard in cultivating awareness of what is happening aroundus with the aim of achieving a happy and serene life.